Phytochemical composition and antioxidant activity of coconut cotyledon. Issue 2 (February 2020) - Nyayiru Kannaian, Udaya Prakash; Edwin, Jasmine Brighty; Rajagopal, Vidhya; Nannu Shankar, Sripriya; Srinivasan, Bhuvaneswari
Abstract: Coconut tree ( Cocos nucifera L.), a perennial, monocot tree, belonging to the family Arecaceae, is distributed through the tropics. Bioactivities of coconut water, husk fiber, oil, flowers, spadix and mesocarp of coconut fruit are widely reported. However, there is no study on cotyledon of coconut. In this study, carbohydrates, proteins, lipids, phenols, flavonoids, tannins, alkaloids and antioxidants were quantified in hot and cold percolated extracts of coconut cotyledon. Further, the antioxidant activity was studied using 2, 2-diphenyl-1-picrylhydrazyl (DPPH); ferric reducing antioxidant power (FRAP); ferric thiocyanate (FTC); thiobarbituric acid (TBA); nitric oxide (NO) radical scavenging and β-carotene bleaching assays. Among the secondary metabolites, only cardiac glycosides were detected. Methanolic extraction by cold percolation extracted high content of secondary metabolites and exhibited significant antioxidant activity in DPPH, FRAP, NO and β-carotene bleaching assays, with EC50 of 0.12, 6.43, 16.21 and 8.09 mg/ml respectively. The chloroform extracts recorded high lipid content and scavenged the radicals in FTC (EC50 13.31 mg/ml) and TBA (EC50 9.21 mg/ml) assays. The study recommends extraction of compounds using methanol through cold percolation. The cotyledon of coconut is found to be a potent nutritive source equivalent to the endosperm. Abstract : Coconut; Cotyledon; Cold percolation; Cardiac glycosides; Antioxidant; Biochemical composition of food; Plant products; Phytochemistry; Bioactive plant product; Secondary metabolite; Food science